2020
DOI: 10.3390/atmos11080872
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Synoptic Climatology of Lake Erie and Lake Ontario Heavy Lake-Effect Snow Events

Abstract: Lake-effect snow (LES) storms pose numerous hazards, including extreme snowfall and blizzard conditions, and insight into the large-scale precursor conditions associated with LES can aid local forecasters and potentially allow risks to be mitigated. In this study, a synoptic climatology of severe LES events over Lakes Erie and Ontario was created using an updated methodology based on previous studies with similar research objectives. Principal component analysis (PCA) coupled with cluster analysis (CA) was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 44 publications
(108 reference statements)
4
28
0
Order By: Relevance
“…[20]) form during LES events. This was observed in [35] and [36] who found that, for a PBL thermodynamic profile conducive to LES formation, subtle variations in the surface dipole structure driven by deviations in the synoptic scale pattern led to varying LES snow band types and impacts.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…[20]) form during LES events. This was observed in [35] and [36] who found that, for a PBL thermodynamic profile conducive to LES formation, subtle variations in the surface dipole structure driven by deviations in the synoptic scale pattern led to varying LES snow band types and impacts.…”
Section: Introductionmentioning
confidence: 77%
“…Additionally, as the clipper propagates and matures, an anticyclone will typically build in its wake which creates a pressure dipole and tight isobaric gradient between the two pressure systems. As [35,36] note, in addition to strong flow, this dipole has also been linked with LES off the Great Lakes.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations